ISOLASI DAN IDENTIFIKASI SENYAWA YANG BERSIFAT ANTIBAKTERI DAN TOKSIK DALAM TUMBUHAN ILER {Coleiis scutellarioides [L.] Benth) - Tungga , Dionisius; Swantara , I Made Dira; Ciawi, Yenni (AGRICA, 2008)
The isolation and identification of antibacterial and toxic compound on Coleiis scutellarioides [L.] Benth. has been conducted. The extraction applied was maceration method using ethanol 85 %. The ethanol extract then partitioned using three kinds of solvents namely n-hexane, chloroform, ethyl acetate respectively. The most toxic and active antibacterial extraction was separated by chromatography column with n-hexane: chloroform as the mobile phase. Identification of the active isolate was conducted by gas chromatography-mass spectroscopy with the aim of'Wiley 229.L database. Toxic test and antibacterial activity test showed that FB2 was proved to be the most toxic and active antibacterial one. The most toxic and active antibacterial fraction of FB2 showed a retardation area of 66,98 mm2 to Micrococcus luteus and 54,43 mm2 to Escherichia coli, and LC50 at 90,72 ppm. Gas chromatography-mass spectroscopy data show that the FB2 fraction contains 4 compounds namely palmitate acid (24,41%); stearate acid (19,53%); 9-oktadekenamida (22,95%); and Esther dioctyl hexadioat (33,11 %Â»)â€¢